ANALISIS PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA PENCEMARAN NAMA BAIK MELALUI FACEBOOK - Iftita Zahra Anggraeni; Harjono Harjono (Sebelas Maret University, 2023)
This article was written with the aim of knowing the judge's considerations in deciding a defamation case via Facebook based on Decision Number: 303/Pid.Sus/PN Tbt. The method used in this research is normative or docryal which is prescriptive and applied with a case approach. Techniques for collecting primary and secondary legal materials are obtained from document studies or literature. The law material analysis technique used is the syllogism method which uses a deductive mindset. Based on the results of the research and discussion it is known that the judge's considerations in deciding the criminal act of defamation through Facebook are in accordance with the elements in Article 45 paragraph (3) Jo. Article 27 paragraph (3) Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions. The judge in deciding the case has used at least 2 (two) valid pieces of evidence in accordance with Article 184 of the Criminal Procedure Code, namely witness statements, expert statements, and defendant statements.Keywords: Judge's consideration; Defamation; Evidence